Karakteristik Pendampingan Orang Tua Dalam Kedisiplinan Belajar Anak Masa Pandemi Di Desa Ketip Juwana - Zulfayanti, Indana Fatikha; Purbasari, Imaniar; Masfu'ah, Siti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The limited time for students to study at school due to the Covid-19 pandemic has reduced the level of student learning discipline. Not only students who lack discipline, sometimes parents are also less disciplined with time. Sometimes their children's assignments, which should be collected on the day of taking a new assignment, are not collected by their parents because of several obstacles which are the reasons for the parents. The purpose of this study is to describe student learning discipline and the process of assisting parents in improving student learning discipline during the Covid-19 pandemic in Ketip Juwana Pati village. This research uses a narrative qualitative research type with the research subjects namely parents of students and students. Data collection techniques include the stages of observation, interviews, documentation. Data analysis includes data collection, data reduction, data presentation, data verification or drawing conclusions. Good learning discipline can also be seen by students who have good attention when studying in online classes, students seriously follow the explanations of the teacher when studying online. The process of assisting parents in improving student learning discipline during the Covid-19 pandemic in Ketip Juwana Pati village was carried out by providing learning facilities, for example, meeting all the needs of children's online schools, including buying quotas for online learning. Parents also supervise children's learning activities at home, participate in paying attention to children's learning activities in online classes and parents monitor whether children have done assignments from the teacher. Parents guide while studying online at home